Design and Validation of a Human Brain Endothelial Microvessel-on-a-Chip Open Microfluidic Model Enabling Advanced Optical Imaging - Salman, Mootaz M.; Marsh, Graham; Kusters, Ilja; Delincé, Matthieu; Di Caprio, Giuseppe; Upadhyayula, Srigokul; de Nola, Giovanni; Hunt, Ronan; Ohashi, Kazuka G.; Gray, Taylor; Shimizu, Fumitaka; Sano, Yasuteru; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
We describe here the design and implementation of an in vitro microvascular open model system using human brain microvascular endothelial cells. The design has several advantages over other traditional closed microfluidic platforms: (1) it enables controlled unidirectional flow of media at physiological rates to support vascular function, (2) it allows for very small volumes which makes the device ideal for studies involving biotherapeutics, (3) it is amenable for multiple high resolution imaging modalities such as transmission electron microscopy (TEM), 3D live fluorescence imaging using traditional spinning disk confocal microscopy, and advanced lattice light sheet microscopy (LLSM). Importantly, we miniaturized the design, so it can fit within the physical constraints of LLSM, with the objective to study physiology in live cells at subcellular level. We validated barrier function of our brain microvessel-on-a-chip by measuring permeability of fluorescent dextran and a human monoclonal antibody. One potential application is to investigate mechanisms of transcytosis across the brain microvessel-like barrier of fluorescently-tagged biologics, viruses or nanoparticles.